Advanced control of optical disk drive servos - Dong, Fengdan (2008)
This thesis presents research results on advanced control of Optical Disk Drive (ODD) servos. It first presents brief introduction of optical disk technology (ODD), as well as magnetic technology (HDD), and later on, gives a general description of the ODD servomechanism, which is dual-stage actuator.